Entropy-stabilized silicides: Expanding the B20 single-phase region from mono-silicide to high-entropy silicide - Sang Jun Kim; Kook Noh Yoon; Won-Seok Ko; Eun Soo Park (APL Materials, 2022)
The formation of a single phase is an important requirement for high-entropy ceramics (HECs) because precipitation of unwanted phases generally degrades their functional properties. This paper provides a useful guideline for the single-phase formation of HECs. First, metal elements constituting HECs can be divided into two groups: elements that have a parent phase as a stable phase and elements that have a phase with the same stoichiometry as the parent phase but a different crystal structure. Second, even when the latter elements are added in an HEC, we can stabilize the parent phase if stabilizing energy by configurational entropy is larger than the difference in formation energy due to their stable phase, which can be quantitatively calculated through first-principles calculation. Interestingly, based on these guidelines, (CrMnFeCoNi)Si HE silicide with a single B20 structure was sequentially developed from mono-silicide. In particular, the HEC with maximized configurational entropy was searched in our HEC system by adding NiSi to (CrMnFeCo)Si, which is stable in B31 and B20 structures. This study offers a chance to increase the structural and compositional complexity in HECs, enabling the expansion of the single-phase region in HECs.